1994
DOI: 10.2307/3578708
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Thermoradiosensitization in Two Human Melanoma Cell Lines and One Fibroblast Cell Line by Concurrent Mild Hyperthermia and Low-Dose-Rate Irradiation

Abstract: Two human melanoma cell lines, one radioresistant (SK-MEL-3) and one radiosensitive (HT-144), and a normal human fibroblast line (AG1522) were evaluated for thermoradiosensitization of low-dose-rate irradiation by concurrent mild hyperthermia (39-41 degrees C). None of the cell lines expressed chronic thermotolerance during heating at 39-41 degrees C. The SK-MEL-3 cells were the most heat sensitive, while AG1522 and HT-144 cells had the same sensitivity at 39 and 40 degrees C but HT-144 cells were more sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Since most basic research in hyperthermia oncology has been performed on rodent cells (Hahn 1982, Hall 1994, it is important to evaluate the interaction between heat and LDRI in human cell lines because the heat dependent response of human cell lines is substantially different from that of rodent cell lines (Raaphorst and Azzam 1983, Hahn et al 1989, Raaphorst et al 1989, Roizin-Towle and Pirro 1991, Mackey et al 1992a, Armour et al 1993. Recent research studies have indicated that, in comparison with rodent cells, most human cells are more resistant to higher temperature >42"C (Hahn et al 1989, Raaphorst et al 1989, Roizin-Towle and Pirro 1991 but are more sensitive to lower temperature, long duration mild hyperthennia (Mackey et al 1992a, 1992b, Armour et al 1993.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most basic research in hyperthermia oncology has been performed on rodent cells (Hahn 1982, Hall 1994, it is important to evaluate the interaction between heat and LDRI in human cell lines because the heat dependent response of human cell lines is substantially different from that of rodent cell lines (Raaphorst and Azzam 1983, Hahn et al 1989, Raaphorst et al 1989, Roizin-Towle and Pirro 1991, Mackey et al 1992a, Armour et al 1993. Recent research studies have indicated that, in comparison with rodent cells, most human cells are more resistant to higher temperature >42"C (Hahn et al 1989, Raaphorst et al 1989, Roizin-Towle and Pirro 1991 but are more sensitive to lower temperature, long duration mild hyperthennia (Mackey et al 1992a, 1992b, Armour et al 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research studies have indicated that, in comparison with rodent cells, most human cells are more resistant to higher temperature >42"C (Hahn et al 1989, Raaphorst et al 1989, Roizin-Towle and Pirro 1991 but are more sensitive to lower temperature, long duration mild hyperthennia (Mackey et al 1992a, 1992b, Armour et al 1993. Mackey et al (1992aMackey et al ( , 1992b demonstrated that HeLa cells were more sensitive to mild hyperthermia than Chinese hamster ovary cells.…”
Section: Discussionmentioning
confidence: 99%
“…When combined LDMH/LDR therapy was applied to several human cell lines with a variety of heat and radiation sensitivities, LDR sensitization was observed in all with the largest degree of sensitization occurring in the most radiation resistant cell type 17,18 . In these studies, it was also shown that the most resistant cell lines had a greater capacity for repair of sublethal radiation damage and thus inhibition of sublethal damage repair (SLDR) by LDMH-enhanced radiosensitization in such cells, thereby overcoming resistance.…”
Section: Long Duration Hyperthermia and Low Dose-rate Brachytherapy: mentioning
confidence: 99%
“…At this time, cells were in an actively proliferating phase, as judged from growth curves [5] and flow-cytometric measurements [27]. Plateau-phase cultures were obtained by seeding the same number of cells, incubating them under identical conditions for 5 days, completely replacing the medium and then using them for experiments 3 days later [5,28].…”
Section: Cell Culture Conditionsmentioning
confidence: 99%